2010
DOI: 10.1108/09513541011080011
|View full text |Cite
|
Sign up to set email alerts
|

The practice of co‐creating leadership in high‐ and low‐performing high schools

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As said earlier, other researchers have documented the significance of dispositions and conditions that facilitate learning. Jarrett et al (2010) found that high-performing high schools had a significantly higher prevalence of the practice of co-creating leadership dispositions and the presence of institutional conditions that facilitate student learning. Quinn (1992) found that quality products largely depended on the sharing of tacit knowledge.…”
Section: Reflectionmentioning
confidence: 97%
See 2 more Smart Citations
“…As said earlier, other researchers have documented the significance of dispositions and conditions that facilitate learning. Jarrett et al (2010) found that high-performing high schools had a significantly higher prevalence of the practice of co-creating leadership dispositions and the presence of institutional conditions that facilitate student learning. Quinn (1992) found that quality products largely depended on the sharing of tacit knowledge.…”
Section: Reflectionmentioning
confidence: 97%
“…Researchers in these areas have documented the benefits of these constructs. For example Jarrett, Wasonga, and Murphy (2010) documented a higher preponderance of the practice of leadership dispositional values in high-performing high schools. Getzels and Guba (1957) found higher levels of individual fulfilment and performance output when institutions provided favorable work environments.…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation